Analysis of The Level of Compliance With Employee Safety Behavior at PT. X Uses The Behavior-Based Safety (BBS) Method - Sangkala, Rahul Ibrahim; Saputra, Reza Atilansyah; Saputra, Arya Dwi; Aditya, Rayzhan; Friber, Friber; Iroth, Alessandro Natanael; Hauzan, Irsyad; Malik, Anis Rohmana (Jurnal Multidisiplin Indonesia, 2024)
Behavior-based safety (BBS) programs are a safety approach based on human behavior and social relationships in the work environment. This approach aims to increase employee awareness, commitment and responsibility to create a safer and healthier work environment. A behavior-based safety (BBS) approach focuses on human behavior to reduce the risk of workplace accidents and injuries. This research uses a qualitative approach that combines observation and interview methods. This approach was chosen to gain a deeper understanding of the safety behavior of PT employees. X and the factors that influence it are observed directly in the PT work environment. X observes employee safety behavior in real-life situations. Dangerous behavior is the behavior of an individual or group of workers that can create a dangerous situation in a work process. Implementation of security in the PT environment. X has been around since the company's inception, but safety was only documented around 2022. work without complete PPE. Employees in the company already understand SMK3. Strengthen safety training, implementation and monitoring of safety procedures, safety culture, risk assessment, effective incident reporting systems, regulatory enforcement and discipline.